Les paysages végétaux du djebel Mégriss (Tell septentrional, Algérie) : diversité des écosystèmes, richesse floristique, ampleur de l'anthropisation - Nacira Boulaacheb (Physio-Géo)
Between the little Kabylia, in the North, the Hodna, in the South, and the Aurès, in the southeast, extends the High Plains within the Sétif Province. In these vast plains, semi-arid, several mounts are isolated. The djebel Megriss, represents one of the most important mounts of the north part of these High Plains. It plays the role of a geographical barrier, by decreasing the influences of the South on the neighbouring mounts, in particular the mounts of Djurdjura and Babors. It can also be at the origin of phenomena of biological isolation, which drove to the preservation of relics in very located biotopes (temporary ponds).Its ecosystem is extremely heterogeneous in terms of environment, with characteristic grassland, meadows, low shrubland consisting of Quercusilex and low shrubland consisting of Calicotome and Ampelodesmos ("diss grass"); a peculiarity is the presence of temporary ponds, sources, temporary streams, meadows flooded in winter and meadows dominate by Juncus and Carex.This variety of environment played a big role in the variety of the flora where 500 botanical species (Phanerogams and vascular Cryptogams) and 22 subspecies were listed belonging to 276 genres and 72 families.Among the botanical species vascular listed, 40 % are of Mediterranean origin, 24 % are septentrional, 19 % are species of transition between the Mediterranean element and the other elements, 10 % are endemic, 5 % are cosmopolitan and 2 % are tropical.Two of the peculiarities of the flora of the massif are, on one hand, its wealth in orchids, in particular in Dactylorhiza, present mainly in the boreal and temperate zones of the globe, and, on the other hand, the presence of numerous rare species and belonging to the other sectors than the Constantine region to which belongs djebel Megriss (Butomusumbellatus, Myosorusminima, Brunella laciniata, etc.).The ecosystem is affected by many menaces (cultivation, repeated passage, harnessing of the water, the picking, the distribution of intrusive species, pollution).